The Novel J-Domain Protein Mrj1 Is Required for Mitochondrial Respiration and Virulence in Cryptococcus neoformans - Linda C. Horianopoulos (American Society for Microbiology, 2020)
ABSTRACT The opportunistic fungal pathogen Cryptococcus neoformans must adapt to the mammalian environment to establish an infection. Proteins facilitating adaptation to novel environments, such as chaperones, may be required for virulence. In this study, we identified a novel mitochondrial co-chaperone, Mrj1 (mitochondrial respiration J-domain protein 1), necessary for virulence in C. neoformans. The mrj1Δ and J-domain-inactivated mutants had general growth defects at both routine laboratory and human body temperatures and were deficient in the major virulence factor of capsule elaboration. The latter phenotype was associated with cell wall changes and increased capsular polysaccharide shedding. Accordingly, the mrj1Δ mutant was avirulent in a murine model of cryptococcosis. Mrj1 has a mitochondrial localization and co-immunoprecipitated with Qcr2, a core component of complex III of the electron transport chain. The mrj1 mutants were deficient in mitochondrial functions, including growth on alternative carbon sources, growth without iron, and mitochondrial polarization. They were also insensitive to complex III inhibitors and hypersensitive to an alternative oxidase (AOX) inhibitor, suggesting that Mrj1 functions in respiration. In support of this conclusion, mrj1 mutants also had elevated basal oxygen consumption rates which were completely abolished by the addition of the AOX inhibitor, confirming that Mrj1 is required for mitochondrial respiration through complexes III and IV. Furthermore, inhibition of complex III phenocopied the capsule and cell wall defects of the mrj1 mutants. Taken together, these results indicate that Mrj1 is required for normal mitochondrial respiration, a key aspect of adaptation to the host environment and virulence. IMPORTANCE Cryptococcus neoformans is the causative agent of cryptococcal meningitis, a disease responsible for ∼15% of all HIV-related deaths. Unfortunately, development of antifungal drugs is challenging because potential targets are conserved between humans and C. neoformans. In this context, we characterized a unique J-domain protein, Mrj1, which lacks orthologs in humans. We showed that Mrj1 was required for normal mitochondrial respiration and that mutants lacking Mrj1 were deficient in growth, capsule elaboration, and virulence. Furthermore, we were able to phenocopy the defects in growth and capsule elaboration by inhibiting respiration. This result suggests that the role of Mrj1 in mitochondrial function was responsible for the observed virulence defects and reinforces the importance of mitochondria to fungal pathogenesis. Mitochondria are difficult to target, as their function is also key to human cells; however, Mrj1 presents an opportunity to target a unique fungal protein required for mitochondrial function and virulence in C. neoformans.